THE TECHNOTYPOLOGICAL ANALYSIS OF THE JESUIT INFLUENCE/INTERFERENCE GUARANI CERAMICS AT THE ARCHAEOLOGICAL SITES ALVIM, CASTELINHO AND TAQUARUÇU (Interdisciplinary Studies Journal, 2023)
This article aims to analyze the characteristics of Jesuit interference/influence of the Archaeological Sites Alvim (Pirapozinho – SP), Castelinho (Presidente Epitácio – SP) and Taquaruçu (Sandovalina – SP), through the operative chain of La Salvia and Brochado (1989) and Faccio's technotypological model (1992), as well as a bibliographical review of Jesuit Reductions and contact with the Guarani. From the Treaty of Tordesillas, in 1494, which aimed to divide the “world” by an imaginary line between the two greatest powers of the 15th century – Portugal and Spain – the Jesuit Reductions were established in search of the “spiritual salvation” of the indigenous peoples and the demarcation of the Spanish border territory, in order to stop the expansion of the Portuguese over the region of the River Plate. Thus, a new organization of space reached the Guarani way of life, changing the social structure of the villages, the division of labor and even the material culture of the indigenous people. Thus, it was possible to identify in the archaeological sites the presence of brushed plastic decoration, red engobe on the internal and external face, appendices, flat lips and pedestal vase, which are characterized, by the literature, as having a Jesuit influence. Also, this article discusses the term “influence” and adds another noun, with the aim of highlighting the violence suffered by the Guarani indigenous people, from the invasion, colonization and catechization of their peoples.
Keywords: Guarani Ceramics; Jesuit Reductions; Jesuit Influence; Colonial Brazil